TRANSPORT NEODYMIUM(III) FROM MONAZITE USING TUBULAR SUPPORTEDLIQUID MEMBRANE (TSLM) - Margaretha Laurence (NIM : 10508021); Pembimbing :Dr. Aminudin Sulaeman, MS. , Mellisa
One of the main source of Rare Earth Elements (REE) is monazite(Ln,Th)(PO4) which a by product of tin processing. Neodymium is one of abundant element in monazite compound after cerium and lanthanum. This element was used a lot for glass material either magnet. In this research, Nd(III) and others REE(III) from destruction of monazite with KOH was separated from non-REEs with tubular supported liquid membrane (TSLM). Before separated with TSLM, monazite sample was processed in a few step. First, monazite was destructed with KOH, second step, both of thorium and uranium was separated, and third is oxidation of Ce(III) into Ce(IV) with KMnO4 and the last is separating with TSLM. TBP and D2EHP was acted as a carrier liquid with some variation in kerosene solvent for this research. Optimization of separating process of REE(III) was done by adjusting of feed phase at pH 3. The HNO3 was acted as a stripping solution. A few factors were studied in the optimization of the separation of Nd(III) is by varying: carrier composition in membrane phase, the concentration of HNO3 in stripping phase and REEs(III) concentration in feed phase. The measurement of REEs concentration was done by UV-Vis spectrophotometer with 528 nm wavelength, after having colored complex with alizarin sulphonate. Based on these parameters, the best condition of REEs transport was earned at HNO3 0,1 M, composition of carrier TBP:D2EHP = 0,25M:0,75M and REE(III) concentration in feed phase at 1168 ppm. At this condition, the amount of REE that was successfully transferred from feed phase to stripping phase is 94,54%.